DETERMINAN TAX AVOIDANCE PADA PERUSAHAAN CONSUMER NON-CYCLICALS TAHUN 2022-2024 - Michelle Michelle; Randy Kuswanto (UNIVERSITAS DHARMAWANGSA, 2026)
By analyzing non-cyclical consumer sector businesses listed on the Indonesia Stock Exchange from 2022-2024, this study aims to determine how they avoid paying taxes. Several criteria will be examined to achieve this objective: company size, profitability, corporate governance, leverage, and fixed asset intensity. Financial statements and annual reports are the primary sources of secondary data used in this study, which is a quantitative approach. Researchers used a purposive selection method to select 75 businesses for analysis, and they recorded 225 observations. After collecting the data, they used IBM SPSS to run multiple linear regressions. The study found that tax avoidance was significantly influenced by profitability, but not by leverage, fixed asset intensity, company size, and good corporate governance as assessed by an independent commissioner. The study concluded that, for non-cyclical consumer sector companies, the ability to generate profits is prioritized over other factors when deciding how to avoid paying taxes.